Design feature combinations effects of running shoe on plantar pressure during heel landing: A finite element analysis with Taguchi optimization approach - Yang, Zihan; Cui, Chuyi; Wan, Xianglin; Zheng, Zhiyi; Yan, Songhua; Liu, Hui; Qu, Feng; Zhang, Kuan (Frontiers in Bioengineering and Biotechnology, 2022)
Large and repeated impacts on the heel during running are among the primary reasons behind runners’ injuries. Reducing plantar pressure can be conducive to reducing running injury and improving running performance, and is primarily achieved by modifying the design parameters of running shoes. This study examines the effect of design parameters of running shoes (i.e., heel-cup, insole material, midsole material, and insole thickness) on landing peak plantar pressure, and determines the combination of different parameters that optimizes cushion effects, by employing the Taguchi method. We developed the foot-shoe finite elements (FE) model through reverse engineering. Model assembly with different design parameters was generated in accordance with the Taguchi method orthogonal table. The effectiveness of the model was verified using the static standing model in Ansys. The significance and contribution of different design parameters, and the optimal design to reduce plantar pressure during landing, was determined using the Taguchi method. In descending order of percentage contribution was a conforming heel-cup (53.18%), insole material (25.89%), midsole material (7.81%), and insole thickness (2.69%). The more conforming heel-cup (p < 0.001) and softer insole (p = 0.001) reduced heel pressure during landing impact. The optimal design of running shoe in this study was achieved with a latex insole, 6 mm insole thickness, Asker C-45 hardness midsole, and 100% conforming heel-cup. The conforming heel-cup and the insole material significantly affected peak plantar pressure during heel landing. The implementation of a custom conforming heel-cup is imperative for relieving high plantar pressure for long-distance heel-strike runners.